THU0178 Comprehensive Disease Control with Golimumab in Patients with Rheumatoid Arthritis. (23rd January 2014) - Combe, B.; Veale, D.; Burgos-Vargas, R.; Szűcs, G.; Leirisalo-Repo, M.; Yao, R.; Govoni, M.; Vastesaeger, N.; Weng, H. H.
Abstract : Background: Comprehensive management of rheumatoid arthritis (RA) involves clinical goals such as remission and low disease activity (LDA) and outcomes important to patients such as daily functioning and minimization of pain. Objectives: To evaluate comprehensive disease control with 6 months of add-on golimumab (GLM) treatment in a broad sample of patients with active RA despite disease-modifying antirheumatic drugs (DMARDs). Methods: GO-MORE was an open-label, multinational, prospective study in biologic-naïve patients with active RA (DAS28-ESR ≥3.2) despite DMARD treatment. Patients received 50-mg SC GLM once monthly for 6 months. Patients completed the Health Assessment Questionnaire Disability Index (HAQ-DI) and patient acceptable symptom state (PASS). PASS was assessed with one yes/no question as to whether the patient would be satisfied to stay in their current disease state. Effects of baseline disease activity on DAS28-CRP, remission, and LDA (based on DAS28-ESR and simplified disease activity index [SDAI]) were evaluated with chi-square tests. Results: Among 3280 efficacy-evaluable patients, the baseline mean age was 52.3 (SD=12.8) years, and mean disease duration was 7.63 (SD=7.903) years. The baseline mean DAS28-ESR, DAS28-CRP, and HAQ-DI values were 5.97 (SD=1.10), 5.41 (SD=1.00), and 1.44 (SD=0.67), respectively. At baseline, 21.3% of patients had moderate disease activity (DAS28-ESR EULAR 3.2 to 5.1), and 78.7% had high disease activity (DAS28-ESR EULAR >5.1). At month 6, remission based on DAS28-ESR and SDAI was attained by 23.9% and 14.2% of patients, respectively. LDA based on DAS28-ESR and SDAI was reached by 37.4% and 48.3% of patients, respectively, at month 6. Month 6 DAS28-CRP levels of <2.6 or 2.6 to <3.2 occurred in 32.5% and 49.5% of patients, respectively. Patients with moderate baseline disease activity were more likely to reach remission or low disease activity state than those with high baseline disease activity (Table). At month 6, PASS and minimal or no functional impairment (HAQ-DI ≤0.5) were achieved by 66.0% and 37.4% of patients, respectively. Conclusions: In patients who had inadequate control of RA with a variety of nonbiologic DMARDs, 6 months of add-on treatment with once-monthly GLM resulted in good comprehensive disease control as measured by composite indices of clinical activity and patient-reported outcomes. Disclosure of Interest: B. Combe Grant/research support from: Pfizer, Roche-Chugai, Consultant for: Merck, Pfizer, Roche-Chugai, and UCB, D. Veale Grant/research support from: Abbott, MSD, Pfizer and Roche, Consultant for: MSD, Pfizer, Roche and UCB, Speakers bureau: MSD, Pfizer, Roche and UCB, R. Burgos-Vargas: None Declared, G. Szűcs: None Declared, M. Leirisalo-Repo Consultant for: MSD, R. Yao Employee of: Merck, M. Govoni Employee of: Merck, N. Vastesaeger Employee of: Merck, H. Weng Employee of: Merck